Fighting Stereotypes: Expressions of Femininity in Public Spaces and the Challenge of Toxic Masculinity - Zega, Okto David Kristian; Koritelu, Paulus; Murwani, Prapti (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores the dynamics of toxic masculinity and its impact on gender expression in public spaces in Negeri Rumahtiga, a community characterized by strong patriarchal structures. Employing a qualitative research design, data were collected through in-depth interviews, participant observations, and document analysis to uncover how hegemonic masculinity manifests and shapes individual behaviors. Findings indicate that toxic masculinity in public spaces harms not only women but also men who deviate from dominant masculine ideals, leading to psychological strain and social exclusion. Expressions of femininity in public are often met with ridicule or suppression, while men are pressured to conform to rigid expectations of strength, emotional restraint, and heterosexuality. This research highlights that masculinity is a socially constructed and contested identity, not an innate male trait. The study offers new insights by addressing the psychological consequences of toxic masculinity on men—an area often overlooked in previous literature. It recommends that sociocultural interventions and inclusive gender discourse are essential to challenging entrenched stereotypes and promoting gender justice. This contribution enhances the understanding of gender construction in localized contexts and supports broader efforts within social sciences and humanities to address structural inequalities and promote emancipatory social change.